AB0703 Long term follow-up of behÇet's syndrome patients treated with cyclophosphamide. (12th June 2018) - Gurcan, M.; Esatoglu, S.N.; Hamuryudan, V.; Saygin, C.; Saygin, D.; Ugurlu, S.; Seyahi, E.; Fresko, I.; Melikoglu, M.; Yurdakul, S.; Yazici, H.; Hatemi, G.
Abstract : Background: Cyclophosphamide (CYC) remains an important treatment option for Behçet's syndrome (BS) patients with life-threatening conditions such as arterial aneurysms. However, several adverse events may occur with CYC and this has led to increased use of biologic agents such as rituximab in other vasculitides. Objectives: The aim of this study is to delineate the outcome and short and long-term adverse events with CYC use among BS patients. Methods: We conducted a retrospective chart review of all BS patients treated with oral or intravenous CYC between 1976 and 2006. Patients were called and a standard form was used for collecting demographic characteristics, CYC indication, cumulative dose of CYC and short-term serious adverse events necessitating the cessation of therapy and/or requiring hospitalisation and long-term adverse events (malignancy and infertility), and outcome. Results: We identified 198 (M/W: 184/14) BS patients who had received CYC. After a median follow up of 17 (IQR: 9–26) years after the initiation of CYC therapy, 52 (26%) patients had died within a median duration of 4 1–12 years, 33 (17%) were lost after a median follow-up of 9 (3.5–14) years, and 113 (57%) were contacted. CYC was prescribed for vascular involvement in 132 (67%) patients, eye involvement in 52 (26%), central nervous system involvement in 5, both vascular and eye involvement in 7 and both vascular and central nervous system involvement in 2 patients. The median duration of CYC use was 12 (IQR:4–24) months and median cumulative dose was 13.5 (IQR:6–49) gr. Among the 52 patients who died, reasons for death were vascular involvement in 26, malignancies in 7, infections in 5 (5 bacterial infections, 1 additional tuberculosis), neurologic involvement in 2, ischaemic stroke in 1, traffic accident in 1, and secondary amyloidosis in 1, esophageal variceal bleeding in 1, and unknown in 5 patients. Sixteen (8%) patients experienced serious adverse events associated with short-term CYC use and 1 of them died due to infection. Among these adverse events, haemorrhagic cystitis occurred in 7 patients, infections in 4 (1/4 died), leukopenia, acute myocardial infarction, anaphylactic reaction, azoospermia, liver toxicity, and severe nausea in 1 patient each. Overall, 16 malignancies were observed in 14 (7%) patients after a median follow up of 25 (IQR:15–26) years. The malignancies were bladder carcinoma (n=4), lung adenocarcinoma (n=3), prostate adenocarcinoma (n=2), carcinoma of unknown primary origin, pancreas adenocarcinoma, t-MDS-AML, lymphoma, colon adenocarcinoma, squamous cell carcinoma and thyroid papillary carcinoma. Among the 113 patients, we were able to question regarding infertility, 67 patients (59%) had children, 22 (19.5%) did not wish to have a child and 24 (21.5%) tried to have a child, but was not able to. Conclusions: Short term serious adverse events occurred in 8% of the patients during CYC treatment. During long term follow-up malignancies occurred in 7% and infertility in 21.5% of the patients. These results underline the need for safer and effective alternatives to CYC for serious organ involvement in BS, similar to that in other vasculitides. Disclosure of Interest: None declared